Effectiveness of Isometric Handgrip Exercise in Reducing Blood Pressure in Hypertension Patients - Umi Margi Rahayu; Bagus Prayitno; S. Eko Ch. Purnomo; Sudiarto Sudiarto (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hypertension is one of the major health problems that can trigger complications of cardiovascular disease. One of the non-pharmacological therapies that has been proven effective in lowering blood pressure is Isometric Handgrip Exercise (IHE). This study aims to analyze the effect of IHE on reducing blood pressure in hypertensive patients in Dusun Bungkel, Grobogan Regency. The design of this study used a quasi-experiment with a time-series approach. A total of 31 respondents were selected using a purposive sampling technique. The IHE intervention was carried out for five consecutive days with a training duration of six minutes per day. Blood pressure was measured before and after each training session. Data were analyzed using paired t-test and Wilcoxon. The results showed that IHE for five days could reduce systolic blood pressure by 21.6 mmHg and diastolic by 13.5 mmHg, with an average decrease per session of 6.5 mmHg for systolic and 4.1 mmHg for diastolic. The results of the statistical test showed a p value <0.05, which means that the decrease in blood pressure was significant.